Needle-related pain and distress management during needle-related procedures in children with and without intellectual disability. - Pascolo, Paola; Peri, Francesca; Montico, Marcella; Funaro, Mishelle; Parrino, Roberta; Vanadia, Francesca; Rusalen, Francesca; Vecchiato, Luca; Benini, Franca; Congedi, Sabrina; Barbi, Egidio; Cozzi, Giorgio (Eur J Pediatr, 2018)
Children with intellectual disability frequently undergo needle-related procedures for diagnosis or treatment. Nevertheless, only a few studies deal with pain and distress management during the procedure in this population of children. This study aimed to investigate the number of anxiety and pain management techniques performed during needle procedure in children with intellectual disability (cases) compared to a population of children without intellectual disability (controls). This multicenter cohort study was performed from July 2016 to January 2018 in the pediatric ward of four urban hospitals in Italy. Eligible subjects were children with and without intellectual disability, from 4 to 17 years old, who needed venipuncture or intravenous cannulation for diagnosis or treatment. Use of topical anesthesia, distraction techniques, and physical or verbal comfort during procedures were recorded. Pain and anxiety scores were also recorded. Forty-seven cases and 94 controls were recruited. Three pain- and anxiety-relieving techniques were performed during the procedure in 12 (25%) cases and in 10 controls (11%); two techniques were performed in 23 (50%) cases and in 26 (28%) controls; 12 (25%) cases and 52 (55%) controls received only one.Conclusion: In this series, children with intellectual disability received significantly more relieving techniques, but experienced more pain and anxiety when compared to children without intellectual disability. What is Known: • Children with intellectual disability experience more episodes of pain than cognitively healthy ones, and almost 10% of these episodes are due to medical procedures. What is New: • Children with intellectual disability despite receiving more relieving techniques during a needle-related procedure experienced more pain and anxiety when compared to healthy children.
Keywords: Adolescent; Anxiety; Child; Child, Preschool; Cohort Studies; Female; Humans; Intellectual Disability; Italy; Male; Pain Management; Pain Measurement; Pain, Procedural; Phlebotomy